Solar Cells: Current State and Development Prospects - I. I. Maronchuk; D. D. Sanikovich; V. I. Mironchuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers the main trends in the development of the world market of solar photovoltaics over the past few years. It is shown that the industry is a very rapidly evolving one among the branches of renewable energy and modern industries as a whole. It is obvious that the prime cost of the of solar energy being produced is rapidly approaching the price of electricity generated by traditional methods at nuclear power plants and thermal power plants. The aspects of the development of the efficiency of modern research solar cells made of various materials using innovative technological solutions based on the data provided by the National Laboratory for Renewable Energy (NREL, USA) in 2017 are noted. For the convenience of analysis, the research solar cells are divided into four technological groups. The advantages and disadvantages of solar cells, including the specific features of their production and prospects for development are considered separately for each group; the maximum efficiency for the year 2017 is estimated. A possible alternative to the future development of modern high-performance single-transition solar cells is the use of fundamentally new materials based on nanoheteroepitaxial structures with quantum dots. The possibilities of absorption (processing) by such structures of both short-wave radiation and long-wave part of the solar radiation spectrum for the purpose of generation of electric energy by increasing the efficiency of solar cells on their basis have been demonstrated. The optimal materials for their production and the principles of action of high-performance solar cells on their basis have been considered. The prospects of manufacturing nanoheteroepitaxial structures with quantum dots by liquid-phase epitaxy with pulse cooling of the substrate have been substantiated.